Association of mental health literacy and depression symptoms among young adolescents in Selangor / Sarbhan Singh Lakha Singh - Sarbhan Singh, Lakha Singh (2020)
Mental health literacy (MHL) relating to depression (depression literacy) is a multifaceted concept comprising of knowledge of depression, help seeking and stigma components, that plays an important role in depression outcomes. The aim of this study was to examine the association of depression literacy components namely knowledge of depression, help seeking, stigmatising attitudes and adequacy of depression literacy with depression symptoms among adolescent in Malaysia. This study reports on the common tools used to examine depression literacy, validation of the MHL and Stigma questionnaire and Centre for Epidemiological Studies Depression scale (CES-D) Malay version questionnaire, findings of the depression literacy components and the association of depression literacy components with depression symptoms among adolescents. To answer the objectives of this study, a systematic review, a validation study and one cross sectional study was performed. The systematic review of studies reporting on tools used to examine depression literacy and findings of depression literacy components was carried out. One validation of tools and a cross sectional study were then conducted among secondary school-going adolescent ages between 12 to 14 years in National Secondary Schools from June to December 2017. The validation study involved 65 adolescents from two schools in the Federal Territory of Kuala Lumpur with aim to validate the MHL and stigma questionnaire and the CES-D Malay version questionnaire. The cross-sectional study involved 1707 adolescents from 46 schools in Selangor and was for the purpose of examining the association of depression literacy components with depression symptoms using the validated MHL and stigma questionnaire and the CES-D iv Malay version questionnaire. The systematic review identified vignette-based methodology as the most commonly (85%) used tools to assess depression literacy. Recognition of depression, symptoms of depression, intention to seek help, source of help and personal stigma were the most commonly reported components of depression literacy. Cronbach’s alpha across all constructs in the MHL and stigma questionnaire ranged from 0.518 to 0.764 indicating acceptable levels of internal consistency. Cohen’s kappa values for majority (59%) of items in the MHL and stigma questionnaire indicated moderate level of agreement (0.41 and above). The CES-D Malay version questionnaire reported no floor and ceiling effect, good internal consistency (Cronbach alpha 0.88) and excellent test re-test reliability analysis (ICC= 0.93; 95% CI 0.851, 0.961). Prevalence of depression symptoms among adolescents was 20.3%. Only a minority of participants were able to correctly recognize depression 60 (3.5%) and were classified as having adequate depression literacy 51 (3.0%). There was no significant association between inadequate literacy and depression. Multivariate analysis further showed keeping a person busy as a helpful first aid action (AOR = 1.75; 95% CI 1.19, 2.59), regard getting out in the sunlight as harmful (AOR = 1.96; 95% CI 1.12, 3.45), would not tell anyone if having a problem (AOR = 3.80; 95% CI 2.55, 5.67), perceive dangerousness towards people with depression (AOR = 1.83; 95% CI 1.13, 2.95), not endorsing family as a source of help (AOR = 2.19, 95% CI 1.02, 4.69), being worried what others might think if help is sought (AOR = 1.67; 95% CI 1.02, 2.75), feeling that nothing can help (AOR=1.66 ; 95% CI 1.01, 2.70) and difficult to get an appointment (AOR=1.85 ; 95% CI 1.07, 3.19), were significantly associated with depression. Several recommendations were made such as integrating the concept of depression literacy into school based mental health services and early screening of depression among adolescents. Keywords: adolescent, mental health literacy, depression